Hospitalization costs with degludec versus glargine U100 for patients with type 2 diabetes at high cardiovascular risk: Canadian costs applied to SAEs from a randomized outcomes trial. (1st January 2021) - Tarride, Jean-Eric; Husain, Mansoor; Andersen, Andreas; Gundgaard, Jens; Luckevich, Maria; Mark, Thomas; Wagner, Lily; Pieber, Thomas R.
Abstract: Objectives: The present cost–consequence analysis compared estimated hospitalization costs in a Canadian setting with insulin degludec (degludec) versus insulin glargine 100 units/mL (glargine U100) in patients with type 2 diabetes (T2D) at high cardiovascular (CV) risk. Methods: Medical terms were mapped across the different vocabularies, in order to assign unit costs from eligible hospital abstracts in Canadian Institute for Health Information data (International Statistical Classification of Diseases and Related Health Problems, 10 th Revision, Canada) to serious adverse events (SAEs; Medical Dictionary for Regulatory Activities) from the randomized DEVOTE trial comparing the two insulins degludec and glargine. Mean annual costs of SAE-related hospitalizations were estimated by treatment, the cost difference (degludec − glargine U100) was bootstrapped to compute confidence intervals (CIs) and p -values, and the cost ratio (degludec/glargine U100) was estimated using a Tweedie distribution. Results: The mean annual cost per patient for SAE-related hospitalizations was 4, 074 CAD with degludec and 4, 569 CAD with glargine U100 (cost difference: −495, 95% confidence interval [CI]: −966; −24, p  = .039), for a cost ratio of 0.89 (95% CI: 0.81; 0.98, p  = .016). Overall, cost ratios from sensitivity analyses varying individual methodological assumptions were consistent with the main analysis. Of the system organ classes from DEVOTE SAEs, cardiac disorders were the largest contributor to the costs savings with degludec versus glargine U100. Conclusions: In patients with T2D at high CV risk, our findings suggest that there are likely to be lower hospitalization costs with degludec versus glargine U100 based on the SAEs observed in DEVOTE and in a Canadian setting.